Diagnosis of Insulin Resistance in Polycystic Ovary Syndrome (Research, Society and Development, 2024)
Polycystic Ovarian Syndrome (PCOS) is a gynecological endocrine disorder that affects the ovulation process and mainly the female fertility. About 50% of the population diagnosed with PCOS presents peripheral Insulin Resistance (IR). This article aims to gather articles with information about the relation of PCOS with the development of IR, focusing especially on diagnosis methods and the formulation of a flowchart to help the detection of this condition. Were used as inclusion criteria the articles meta-analysis type and systematic revision from 2018 onwards. Based on the findings of this revision, PCOS is directly related to development of insulin resistance especially in obese patients, because of the liberation of pro-inflammatory cytokines of adipose tissue. The flowchart developed from this article offers the possibility to help the interpretation of the results from laboratory tests and increase the diagnostic speed of the insulin resistance in patients with PCOS. For the diagnostic, are dosed the basal glucose and insulin index, OGTT and HOMA-IR. In all of the cases, it’s required the clinic evaluation and past history for the diagnosis.